Advances in Computer Science and Engineering - Sarbazi-Azad, H. (Springer, 2017)
This book constitutes the revised selected papers of the 13th International CSI Computer Conference, CSICC 2008 held on Kish Island, Iran, in March 2008. The 84 regular papers presented together with 68 poster presentations were carefully reviewed and selected from a total of 426 submissions.